Dynamite Blasts Marks End of Old Ferry 'Contra Costa' - Vallejo Times-Herald (Vallejo Times-Herald)
The first of a series of dynamite blasts Friday destroyed part of the hulk of the old "Contra Costa," 460-foot ferry which formerly ran between Morrow Cove and Contra Costa county, and which was abandoned after its purpose had been usurped by the contstruction of Carquinez bridge which opened in 1927. This is the first of a series of blast experiments on the hulk ordered by Capt. Claude B. Mayo, academy superintendent. Carrying out his orders, Lt. George W. Myers, maintenance engineer at the Academy, superviced work of demolition experts who inserted charges of stick dynamite in the ferry, with the purpose of blasting the ship's remains into sections. These sections will be dragged to shore with safety and greater facility, and then disposed of, probably through burning.